Using a Choice Experiment (CE) in an Open and Distance Learning (ODL) Context in Malaysia - Chiam , Chooi Chea; Huan, Joshua Tan Juat (2015)
There are approximately 65 private higher education providers in Malaysia as of February 2015. There are several institutions that offer the open and distance learning (ODL) mode as their primary teaching and learning pedagogy (Malaysian Qualifications Agency [MQA], 2015). The flexibility of ODL mode has caused significant competition in the education industry. This is because a high level of flexibility meets the needs of adult learners, as they tend to face more obstacles in their quest for education; they have other commitments in life, such as their family and career. The aim of this study is to investigate the attributes that are mostly valued by ODL learners when choosing an ODL higher education institution in Malaysia and to obtain the marginal value of the selected attributes via the consumers' willingness-to-pay (WTP) price. Although there have been studies on the attributes that influence a student's choice of university, none have used choice experiment (CE) theory, along with WTP measurement and basic multinomial logit (MNL) model, to examine such attributes. The sample for this study was 320 persons who agreed to participate in face-to-face interviews. The results indicated that respondents have the highest WTP when an institution's reputation increases from less satisfactory to satisfactory level (RM1,907.75 to RM1,980.20 per semester) based on basic MNL model. It indicates the respondents in this study placed the highest value on the reputation of the education institutions. The results help ODL education institutions to introduce the right marketing strategy and educational services to influence the selection of education provider and to provide appropriate facilities and services to ODL learners in Malaysia in order to enhance its sustainability in the highly competitive education industry. [ABSTRACT FROM AUTHOR